2022
DOI: 10.26502/jsr.10020269
|View full text |Cite
|
Sign up to set email alerts
|

Use of Voice Recordings in the Consultation of Patients Seeking Genital Gender-Affirming Surgery: An Opportunity for Broader Application Throughout Surgery?

Abstract: Introduction It has been demonstrated that patient memory for medical information is often poor and inaccurate. The use of audio recordings for patient consultation has been described; however, to our knowledge this is the first reported use of audio recordings in consultation for gender-affirming surgery. Our aim was to determine whether, and specifically how, audio recording the consultation of patients presenting for genital gender-affirming surgery would be of benefit to patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…Consequently, we can conclude that participants would appreciate consultation recordings as a means to address their information needs. Moreover, we found that consultation recordings were expected to be particularly beneficial in contexts involving treatment decisions, which is consistent with prior research demonstrating that consultation recordings are useful for decision-making (Dommershuijsen et al, 2019;Kwon et al, 2021;Smith et al, 2022). It is noteworthy that in our sample, similar to findings from previous research (Barr et al, 2018), older patients seem to be less in favour of consultation recordings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, we can conclude that participants would appreciate consultation recordings as a means to address their information needs. Moreover, we found that consultation recordings were expected to be particularly beneficial in contexts involving treatment decisions, which is consistent with prior research demonstrating that consultation recordings are useful for decision-making (Dommershuijsen et al, 2019;Kwon et al, 2021;Smith et al, 2022). It is noteworthy that in our sample, similar to findings from previous research (Barr et al, 2018), older patients seem to be less in favour of consultation recordings.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to participants' positive attitudes toward consultation recordings, our findings align with existing research (Barr et al, 2018;Dommershuijsen et al, 2019;Ivermee and Yentis, 2019;Hack et al, 2021;Petric et al, 2021;Smith et al, 2022). Our study also supports previous research indicating that patients value consultation recordings as a suitable solution to the challenge of recalling and comprehending information from medical encounters (van der Meulen et al, 2008;Tsulukidze et al, 2014;van Bruinessen et al, 2017;Barr et al, 2018;Hyatt et al, 2018;Rieger et al, 2018;Dommershuijsen et al, 2019;Kwon et al, 2021;Petric et al, 2021;Shepherd et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One intervention to address this issue is providing patients with consultation recordings. Several international studies have investigated this intervention, predominantly focusing on cancer patients (Tsulukidze et al, 2014), with the majority of research conducted in the United States (Tsulukidze et al, 2014;Elwyn et al, 2017;Grande et al, 2017;Barr et al, 2018Barr et al, , 2021Joshi et al, 2020;Kwon et al, 2021;Smith et al, 2022), Australia (Lipson-Smith et al, 2016;Moloczij et al, 2017;Hyatt et al, 2018Hyatt et al, , 2020Petric et al, 2021;Ryan et al, 2022), and the United Kingdom (Elwyn et al, 2015;Ivermee and Yentis, 2019;Shepherd et al, 2023). Empirical evidence supporting this intervention reveals a wide range of benefits, which help to meet information needs of patients by improving information recall (van der Meulen et al, 2008;Tsulukidze et al, 2014;Barr et al, 2018;Hyatt et al, 2018;Rieger et al, 2018;Dommershuijsen et al, 2019;Kwon et al, 2021;Petric et al, 2021;Shepherd et al, 2023), increasing feelings of being informed (Dommershuijsen et al, 2019;Hack et al, 2021), and enhancing understanding (van Bruinessen et al, 2017;Barr et al, 2018;Hyatt et al, 2018;Kwon et al, 2021;Shepherd et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence supporting this intervention reveals a wide range of benefits, which help to meet information needs of patients by improving information recall (van der Meulen et al, 2008;Tsulukidze et al, 2014;Barr et al, 2018;Hyatt et al, 2018;Rieger et al, 2018;Dommershuijsen et al, 2019;Kwon et al, 2021;Petric et al, 2021;Shepherd et al, 2023), increasing feelings of being informed (Dommershuijsen et al, 2019;Hack et al, 2021), and enhancing understanding (van Bruinessen et al, 2017;Barr et al, 2018;Hyatt et al, 2018;Kwon et al, 2021;Shepherd et al, 2023). Further benefits include increased patient empowerment (Elwyn et al, 2015;Grande et al, 2017;Hyatt et al, 2020;Smith et al, 2022), facilitation of discussions with family members (Dommershuijsen et al, 2019;Hyatt et al, 2020;Kwon et al, 2021;Petric et al, 2021), heightened satisfaction with care (Pitkethly et al, 2008;Dommershuijsen et al, 2019), improvement in decision-making (Dommershuijsen et al, 2019;Kwon et al, 2021;Smith et al, 2022), and reductions in anxiety and depression (Tsulukidze et al, 2014;Rieger et al, 2018;Smith et al, 2022). Research has explored various ways of implementing this intervention, including patient-led recordings [i.e., patients asking clinicians to record with their own recording device or cell phone (Ryan et al, 2022)], covert recordings (Elwyn et al, 2015;Barr et al, 2018), or pro...…”
Section: Introductionmentioning
confidence: 99%